Os incêndios na interface urbano-florestal: questões metodológicas e de gestão = Fires at the urban-forest interface : methodological and management issues - Bouillon, Christophe (2019)
Wildland urban interfaces (WUI) are expanding, so it is important to shareknowledge and research results, particularly in the fields of humanitiesand economics. In the field of human societies, and vulnerabilities, froman economic point of view, like evaluation of costs and of potential lossesare both needed. An analysis of the governance is important for understandingthe local policies. The relationship with the ecosystem around theWUI is also a key point to assess knowledge inside and around the WUI.Furthermore, information about changes, risk assessment and modelingis of great importance to stakeholders' decisions.